The effect of zinc supplementation on anthropometric measurements in healthy children over two years: a systematic review and meta-analysis - Vahid Monfared; Adel Salehian; Zeinab Nikniaz; Soraiya Ebrahimpour-Koujan; Zeinab Faghfoori (BMC Pediatrics, 2023)
Abstract Background Zinc deficiency is one of the most important micronutrient deficiencies in children that can affect the children’s growth pattern. In this regard, different studies were conducted to assess the effect of zinc supplementation on growth patterns in healthy children. To the best of our knowledge, no systematic review has summarized the results of these studies. So, in the present study, we systematically reviewed the result of the studies that assessed the effect of zinc supplementation on anthropometric parameters in healthy, over 2-year-old children. Methods A systematic search was carried out in PubMed, Scopus, and Web of Science from inception to November 2021. Data were pooled using the random-effects method and were expressed as weighted mean difference (WMD) and 95% confidence intervals (CI). Results The pooled results of eight studies, including 1586 participants, showed that zinc supplementation significantly increases height [(WMD): 0.9, 95% CI: (0.27, 1.52), p < 0.001], weight [(WMD): 0.51, 95% CI: (0.06, 0.97), p < 0.001], height for age (HAZ) [(WMD): 0.07, 95% CI: (0.03, 0.10), p < 0.001]. Also, meta-regression analysis did not reveal any significant association between dose and duration of intervention and anthropometric parameters. Conclusion The present study demonstrates the beneficial effects of zinc supplementation on weight, height, and HAZ.